KORELASI ANTARA EKOSISTEM MANGROVE Rhizophora stylosa. TERHADAP BIOTA AQUATIK DI PULAU PRAMUKA KEPULAUAN SERIBU - Muzani Jalaludin; Dianti Lestari; Marisa Andriani; Miftahul Ulum; Sri Nurviana Mellenia (Jurusan Geografi Fakultas Ilmu Sosial Universitas Negeri Padang, 2020)
Pramuka Island is one of many islands in Kepulauan Seribu, which is the central government of Kepulauan Seribu Regency and part of DKI Jakarta Province. Aside as government center, Pramuka Island is also as rehabilitation center for mangrove ecosystems located in Taman Nasional Kepulauan Seribu (TNKpS). Mangrove ecosystems become a transition zone between terrestrial ecosystems and marine ecosystems in maintaining biological balance in coastal ecosystems. As a biological function, mangroves have a role as a chain in a waters that can support the life of various types of aquatic biota. Not only that, mangroves can also create a good life for aquatic biota and also contribute greatly to balancing the biological cycle in a waters. As in biological functions, mangrove ecosystems have a role as